Effect of Product Quality And Promotion On Purchase Decisions - Tessa Fitrah Nur Fatimah; Arga Sutrisna; Depy Muhamad Pauzy (Journal of Indonesian Management, 2022)
This study aims to determine and analyze the effect of product quality and promotion on purchasing decisions at Skin Crackers Sadulur Tasikmalaya. The method used in this research is quantitative and quality methods with a survey approach. With a total sample of 100 consumers as respondents, the data collected was primary data, data analysis in this study used multiple regression analysis, correlation coefficient and determination coefficient using SPSS software. The results of this study indicate that product quality and promotion simultaneously have a significant effect on purchasing decisions. Partially product quality has a significant effect on purchasing decisions. And also partially promotion has a significant effect on purchasing decisions.